New phenol and chromone derivatives from the endolichenic fungus Daldinia species and their antiviral activities. Issue 36 (29th June 2021) - Zhang, Dewu; Gu, Guowei; Zhang, Bingyuan; Wang, Yujia; Bai, Jinglin; Fang, Yuang; Zhang, Tao; Dai, Shengjun; Cen, Shan; Yu, Liyan
Abstract : Eight phenols including three new ones (1–3 ) and four chromones including two new ones (9 and 10 ) were isolated from endolichenic fungus Daldinia sp. CPCC 400770, and some of them showed significant antiviral activities. Abstract : Three new phenolic metabolites, daldispols A–C (1–3 ), two new chromone derivatives, (5 R, 7 R )-5, 7-dihydroxy-2-methyl-5, 6, 7, 8-tetrahydro-4 H -chromen-4-one (9 ) and (5 R, 7 R )-5, 7-dihydroxy-2-propyl-5, 6, 7, 8-tetrahydro-4 H -chromen-4-one (10 ), together with five known phenolic compounds (4–8 ) and two known chromone compounds (11 and 12 ) were isolated from the endolichenic fungus Daldinia sp. CPCC 400770. Their structures were elucidated on the basis of spectroscopic methods, electronic circular dichroism (ECD), and comparison with reported data. Compounds 1, 3, 4, 9, and 11 exhibited significant anti-influenza A virus (IAV) activities with IC50 values of 12.7, 6.4, 12.5, 16.1, and 9.0 μM, respectively, and compound 8 displayed significant anti-ZIKV activity with inhibitory ratio of 42.7% at 10 μM. The results demonstrated that the fungus Daldinia sp. CPCC 400770 might be a rich source for discovering anti-IAV secondary metabolites as potential novel leading compounds.